Loop-Mediated Isothermal Amplification Label-Based Gold Nanoparticles Lateral Flow Biosensor for Detection of Enterococcus faecalis and Staphylococcus aureus - Wang, Yi; Li, Hui; Wang, Yan; Zhang, Lu; Xu, Jianguo; Ye, Changyun (Frontiers in Microbiology, 2017)
The report describes a simple, sensitive and nearly instrument-free assay for visual and multiplex detection of Enterococcus faecalis and Staphylococcus aureus based on multiple loop-mediated isothermal amplification (mLAMP) and lateral flow biosensor (LFB). Detection and differentiation of the Ef0027 gene (E. faecalis-specific gene) and nuc gene (S. aureus-specific gene) were determined using fluorescein (FITC)-and digoxin-modified primers in the mLAMP process. In the presence of biotin- and FITC-/digoxin-modified primers, the mLAMP yielded numerous biotin- and FITC-/digoxin-attached duplex products, which were detected by LFB through biotin/streptavidin interaction (biotin on the duplex and streptavidin on the gold nanoparticle) and immunoreactions (FITC/digoxin on the duplex and anti-FITC/digoxin on the LFB test line). The accumulation of gold nanoparticles generated a characteristic red line, enabling visual and multiplex detection of target pathogens without instrumentation. The analytical sensitivity, specificity and feasibility of LAMP-LFB technique were successfully examined in pure culture and blood samples. The entire procedure, including specimen (such blood samples) processing (30 min), isothermal reaction (40 min) and result reporting (within 2 min), could be completed within 75 min. Thus, this assay offers a simple, rapid, sensitive and specific test for multiplex detection of E. faecalis and S. aureus strains. Furthermore, the LAMP-LFB strategy is a universal technique, which can be extended to detect various target sequences by re-designing the specific LAMP primers.